Females prefer the calls of better fathers in a Neotropical frog with biparental care. (19th October 2019) - Pettitt, Beth A; Bourne, Godfrey R; Bee, Mark A
Abstract: Male secondary sexual traits potentially function as indicators of direct or indirect fitness benefits to females. Direct benefits, such as paternal care, may be especially important to females in species with biparental care. In an experimental field study of the golden rocket frog ( Anomaloglossus beebei ), a Neotropical species with biparental care, we tested predictions from four hypotheses proposed to explain the evolutionary relationship between male secondary sexual traits and paternal care quality (the "good parent, " "differential allocation, " "trade-off, " and "essential male care" hypotheses). We examined: 1) the influence of paternal care on offspring survival, 2) the relationships between male calls and paternal care, maternal care, and opportunities for males to acquire multiple mates, and 3) female preferences for three acoustic properties of male advertisement calls. Our results reveal that paternal care positively impacts offspring survival, that males producing longer calls also provide higher-quality paternal care in the form of greater egg attendance and territory defense, and that females prefer longer calls. Females did not discriminate among potential mates based on differences in dominant frequency or call rate. These findings, which suggest male advertisement calls are indicators of potential direct benefits to females in the form of paternal care, are consistent with the good parent hypothesis and inconsistent with the trade-off, differential allocation, and essential male care hypotheses. Lay Summary: In golden rocket frogs, a Neotropical species with biparental care, females prefer features of vocalizations that indicate a male's quality as a parent. A male-removal experiment showed that paternal care positively impacts offspring survival. Video and acoustic monitoring suggests that the duration of a male's advertisement calls indicate his willingness to attend egg clutches. A playback experiment showed that females prefer longer calls. These data elucidate evolutionary relationships between male secondary sexual traits and paternal care.